SYSTEM OF STUDENT CAREER GUIDANCE AND SUPPORT OF TALENTED YOUTH AT THE UNIVERSITY - D. A. Troeshestova; O. N. Vasil'eva (Высшее образование в России)
The article substantiates the necessity ofcareer guidance work organization at multidisciplinary regional university. The paper formulates the goals and main tasks of this activity. The authors describe the work of the Career guidance center and the Center for work with gifted youth of the Chuvash State University on the following projects: "University Saturdays", "University for Children", "Engineering Classes", "Minor physical and mathematical faculty of the ChSU", "Teachers - to Production". The article sums up the unique experience ofholding Olympiads and creative project competitions for schoolchildren in cooperation with innovative enterprises ofthe Chuvash Republic.